Self-discipline and identity work in theatre: a study of an Italian theatre production - Cinque, Silvia (2018)
This thesis is the product of a four-year PhD research project grounded in Organisation and Management Theory (OMT). The project examines the relationship between self-discipline and identity work in the precarious and economically challenging setting of theatre through the analytical lens of narrative. The arguments are theoretically informed by a Foucauldian reading of discipline and identity, and they build on the existing critical and interpretivist accounts that discuss these two constructs.